A Comprehensive Geomechanical Study to Understand Drilling Challenges in the Eridu Oil Field, Southern of Iraq - Kareem, Ahmed T.; Almahdawi, Faleh H.M.; Hamada, Ghareb M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
In recent years, the Eridu oil field has emerged as a key player in the petroleum industry in southern Iraq as it is the biggest Iraqi oil discovery in 20 years. Extending along a vast area of 5806 km2, the field has commercial oil reserves in formations such as Mishrif, Nahr Umr, Zubair, and Yamama. However, drilling operations in this field have faced significant challenges, including delays and suspensions caused by wellbore instability. One of the main obstacles encountered during drilling operations in the Eridu oil field is the occurrence of partial losses in weak vugs dolomite formations, as well as issues related to sever borehole instabilities such as drilling in tight holes, caving, and breakout due to shear failure in the borehole wall. To address these challenges, a 1 D Geomechanical model (1-D MEM) was constructed using data from vertical wells to better understand the underlying causes of drilling problems. The findings of the 1-D MEM, particularly in relation to mechanical rock properties, rock Elasticity factors, pore pressure, and fracture gradient complex formations like Tanuma and Mishrif, were instrumented in planning drilling operations for inclined and highly deviated wells. By utilizing open hole well logging data and calibrating the model with various resources of data including drilling observations, core mechanical analyses, and pore pressure measurements, a more accurate assessment of wellbore instabilities was achieved. The analysis revealed that many of the wellbore instabilities, such as pack-off, breakout, and stuck pipe, were attributed to the insufficient mud weight that failed to support the rock in the borehole wall. To avoid these issues, it was determined that a safe mud weight range of 11-12.5 ppg is necessary to prevent wellbore instability in shale formations. The study also highlighted the importance of using proper mud weight to prevent shear failure and other drilling complications. The findings of this study provide insights that can be utilized as a cost-effective tool for planning directional and horizontal drilling operations in the Eridu oil field. The accuracy of the failure criteria and geomechanical model is significantly superior and aligns with the analysis of breakouts observed in the caliper and image logs.